Istotne i charakterystyczne elementy duchowości Matek Pustyni - Turzyński, Piotr (Vox Patrum, 2016)
The desert mothers lived between monks in the fourth and fifth centuries. In Apofthegmata Patrum we have preserved same sayings and stories related to Amma Sarah, Amma Syncletica and Amma Theodora. The subject of this article is Meterikon, the new book published quite recently in Poland, which includes some 600 texts attributed to the mothers of the desert or addressed to them. The author of the collection was Byzantine monk Isaiah, who worked on it at the beginning of 13th century, conscious that no one had compiled “such a feminine book”. A Russian bishop found the Meterikon in Jerusalem in the middle of 19th century, and had a translation made of this “absolute rarity”, which would later be published in Greek as well as Russian. We do have now Italian, German and Polish translation. Meterikon presents spirituality of the desert mothers, which is the same like spirituality of the desert fathers, but has its own special accents. Women on the desert consider themselves as brides of Jesus Christ, who is the centre, model and goal of their live. In the spiritual straggle, which is necessary on the desert, they tried to be brave as man and they showed that courage is not appropriate only for one gender. In the sayings of the desert mothers we so often find encouragement to the silence and meekness that we can tell about deep theology of silence in their thinking.